Clean heating: Reforming taxes and levies on heating fuels in Europe. (February 2023) - Rosenow, Jan; Thomas, Sam; Gibb, Duncan; Baetens, Ruben; De Brouwer, Andries; Cornillie, Jan
Abstract: How much tax should governments add to the prices of the energy that we consume? This question has come sharply into focus, as the reality of the need to decarbonise the buildings sector has become more urgent. Adding taxes and levies to energy prices encourages energy efficiency and raises revenues for governments, which can be dedicated to energy transition projects. But adding them disproportionately to electricity discourages us from investing in electrically powered heat pumps, a key technology in the buildings sector decarbonisation jigsaw. This paper shines a light on the imbalance in energy taxation across almost all European markets and makes the case for reform. We find that environmental costs are rarely well reflected in energy prices; and that the costs of energy transition programmes – and occasionally broader social policies – are overwhelmingly borne by electricity consumers. In this paper we explain the current structure of energy taxes and levies in five key European countries where reform would be beneficial, and set out four ways to rebalance energy taxes and levies, drawing on examples from around the continent. Highlights: First peer-reviewed review of taxes and levies on heating fuels in multiple countries. Environmental costs not well reflected in energy prices in key European countries. Costs of clean energy policy overwhelmingly borne by electricity consumers. Structure of energy taxes and levies in five key European countries. Four ways to rebalance energy taxes and levies using examples from around Europe.